Physician - Patient relationship The present situation and our responsibilities - Rahman, Md Mazibur; Wanaiza; Hassan, Munir (Journal of Dhaka National Medical College & Hospital, 2013)
Abstract not available J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 1-3